EVOLUÇÃO HISTÓRICA (1975-2000) E PROGNÓSTICO DO DESMATAMENTO E DAS EMISSÕES DE CARBONO NO ESTADO DO ACRE, AMAZÔNIA, BRASIL - Scarcello, J. A.; Bidone, E. D.; Lacerda, L. D. (Geochimica Brasiliensis, 2012)